The European Union’s Screening Framework for Foreign Direct Investment: Consequences for External Relations - Witkowska, Janina (Comparative Economic Research. Central and Eastern Europe, 2020)
The Lisbon Treaty gives the European Union (EU) institutions new external competences, including foreign direct investment (FDI) in the common trade policy. Using these competences the European Commission formulated a proposal for a regulation establishing the screening framework for FDI, which entered into force in April 2019. The aim of this paper is to discuss the issue of FDI screening as an element of policies towards FDI applied by developed countries, to assess the justifications for its introduction, as well as the potential consequences of the screening framework for inflowing FDI into the EU. A need to protect the EU’s strategic economic interests in relations with third countries was the reason for the introduction of the new tool at the EU level. The new system of screening FDI inflows into the EU is not centralized. The right to screen remains the sole responsibility of the Member States. The co-ordination mechanism at the level of the EU which has been constructed seems to give guarantees that common interests will be protected. The economic and political consequences of the EU’s screening framework for FDI should be foreseen. Apart from administrative and compliance costs, as well as uncertainty and delays related to investment decision processes, two categories of potential consequences seem to be important. These are the expected reduced access to capital by some Member States, especially the ‘new’ ones, and the worsening of relations with external partners, especially China.